2021
DOI: 10.3390/vaccines9010019
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination and Myo-Pericarditis in Patients Receiving Immune Checkpoint Inhibitors: Investigating the Likelihood of Interaction through the Vaccine Adverse Event Reporting System and VigiBase

Abstract: Background: Evidence on whether the influenza vaccine could exacerbate immune-related adverse events, including myopericarditis (MP), in patients treated with immune checkpoint inhibitors (ICIs), is still conflicting. We explored this issue through a global real-world approach. Methods: We queried the Vaccine Adverse Event Reporting System (VAERS) and VigiBase to retrieve cases of MP in which the influenza vaccine and ICIs were recorded as suspect and were concomitantly reported. For the included cases, causal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In the COVID-19 era, pharmacovigilance plays a crucial role for real-time safety monitoring of pharmaceuticals: the global vaccination campaign exemplifies the importance of post-marketing studies for timely detection of rare but serious AEs such as myocarditis, thrombocytopenia, and cerebral venous sinus thrombosis, which may not be fully appreciated in the pre-marketing setting, especially for medications receiving accelerated conditional approval through the so-called rolling review [ 44 ]. In particular, spontaneous reporting databases, such as the FDA Adverse Event Reporting System (FAERS) and WHO-Vigibase, have been successfully exploited to characterize the safety profile of drugs, thus informing clinical practice for proactive monitoring [ 45 , 46 ].…”
Section: Safety Issuesmentioning
confidence: 99%
“…In the COVID-19 era, pharmacovigilance plays a crucial role for real-time safety monitoring of pharmaceuticals: the global vaccination campaign exemplifies the importance of post-marketing studies for timely detection of rare but serious AEs such as myocarditis, thrombocytopenia, and cerebral venous sinus thrombosis, which may not be fully appreciated in the pre-marketing setting, especially for medications receiving accelerated conditional approval through the so-called rolling review [ 44 ]. In particular, spontaneous reporting databases, such as the FDA Adverse Event Reporting System (FAERS) and WHO-Vigibase, have been successfully exploited to characterize the safety profile of drugs, thus informing clinical practice for proactive monitoring [ 45 , 46 ].…”
Section: Safety Issuesmentioning
confidence: 99%
“…Overall, the median time to onset was [2][3][4][5][6][7][8][9][10][11][12][13][14] days after vaccine injection. Pericarditis onset was delayed compared to myocarditis with a median time to onset of 8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] axillary, sweats and chills, fever, headache) appeared at day 1 (70, 45%), followed at day 3 to 4 by chest pain (107, 68%) and shortness of breath (26, 17%). Electrocardiogram (ECG) was abnormal for 68 (43%) patients with myocarditis and troponin was elevated for 41 (26%).…”
Section: Demographics and Characteristics Of Cases From The Worldwide Vigibasementioning
confidence: 99%
“…[5][6][7] A descriptive analysis of drug associated myopericarditis spontaneous reports in the United States (1990States ( -2018 identified that about 0.1% of the cases were related to vaccines. 8 To date, inflammatory cardiac reactions following vaccination have been mostly reported with live-virus vaccines, such as the smallpox vaccine, 6,9,10 and inactivated influenza vaccines, 11 Cases reports of myocarditis/pericarditis secondary to next-generation vaccine platforms, used to prevent COVID-19, have been reported. [12][13][14][15][16][17] Vaccination is critical to contain the SARS-CoV-2 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory authorities throughout the world then fast-tracked approvals for these vaccines under the emergency use of authorization in December 2020 [1]. Furthermore, companies have been racing to find a vaccine for the coronavirus, which has killed over 1.5 million people and infected more than 65 million since it emerged in China in December of last year [3].…”
Section: Introductionmentioning
confidence: 99%